Reckless Legislation : How Legislators Ignore the Consitution - Bamberger, Michael A. (Book collections on Project MUSE., 2000)
"Bamberger urges legislators to avoid the political motives that lead to "reckless legislation" and recommends that they "make full use of the full panoply of available support services ... for a better and deeper knowledge of the issues raised.""--Jacket.